A Wolfram in Sheep's Clothing: Economic Warfare in Spain and Portugal, 1940-1944 - Hugh Rockoff; Leonard Caruana (Rutgers University, Department of Economics, 2000)
One of the most sustained uses of economic warfare by the United States, at least judged by the variety of means used and the issue at stake, occurred in Spain and Portugal during WWII. We provide an overview of this episode by weaving together findings from the secondary literature and from new research in the Spanish archives. The war evolved through several distinct phases. (1) An oil embargo against Spain, although launched when Germany appeared to be winning the war (July 27 to September 7, 1940), was successful in helping keep Spain neutral because it forced the Franco regime to rethink the costs of joining forces with Germany. (2) Preemptive buying of wolfram (tungsten ore) during the middle years of the war was also successful. It forced the Germans to pay more for and to consume less tungsten, a material crucial for the production of armor, armor- piercing shells, and other war related items. (3) Ironically, a second oil embargo against Spain, undertaken when the Germans were retreating on all fronts (January 22 to May 2, 1944), was less successful. The major goal of this embargo, cutting shipments of wolfram to Germany, was not fully realized, partly because monitoring costs were high. Several special circumstances, in particular the naval blockade and the tendency of sanctions and incentives to push the Salazar and Franco regimes in the directions consistent with their own long-run survival, explain the relative success of the economic war.
Keywords: N1; 330; World War II